The arts in dementia: instrumental and experiential perspectives - Schneider, Justine (Aging & mental health, 2023)
The indirect experience of dementia mediated through the arts shapes our preconceptions, educating us to understand dementia, gaining a deeper appreciation of how it may affect an individual. By contrast dementia research has largely regarded the arts through an 'instrumental' lens. They are treated as complex psychosocial interventions. Evidence from research on the arts and dementia remains piecemeal because most studies are small and not all are well designed. For numerous reasons the arts warrant further evaluation and investigation in relation to their potential impact on people with dementia. That research needs to be better-designed and adequately funded if it is to advance knowledge in this field. This is fraught with difficulties: the arts are dynamic and interactive; the medium (intervention) can be affected unpredictably by those people who engage with it. Many creative activities are deliberately participatory; think of group singing or stand-up comedy. The influence of human variability in relation to arts interventions means that large studies are necessary to control for individual differences. Moreover, few studies of the arts in dementia have been designed adequately to account for the intra-group interaction that is characteristic of many arts activities. Then, there is a lack of clarity around the purpose of the arts in dementia. There is scope for the development and adoption of comprehensive theoretical frameworks to guide research into the arts and dementia. This editorial sets out to clarify some aspects of the arts in dementia in order to pave way for further work.